2019
DOI: 10.1073/pnas.1901310116
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous ribosomal translocation of mRNA and tRNAs into a chimeric hybrid state

Abstract: The authors declare no conflict of interest.Published under the PNAS license.Data deposition: The atomic coordinates and structure factors have been deposited in the Research Collaboratory for Structural Bioinformatics (RCSB) Protein Data Bank, www.rcsb. org (RCSB PDB ID code 6N1D).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 56 publications
(109 reference statements)
3
54
0
Order By: Relevance
“…During translocation, A and P site tRNAs move together with their respective mRNA codons. It has been shown that bacterial EFG is crucial to maintain the mRNA‐tRNA interaction during tRNA movement, as the absence or mutation of EFG leads to increased frameshifting and decreased translocation efficiency (Martemyanov et al , ; Savelsbergh et al , 2000a; Holtkamp et al , ; Peng et al , ; Zhou et al , ). An important parameter to maintain the mRNA reading frame is the interaction of mtEFG1 domain IV with the tRNA‐mRNA module via two apical loops that engage with the minor groove of the codon–anticodon base pairs and with the backbone of the peptidyl‐tRNA (Gao et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…During translocation, A and P site tRNAs move together with their respective mRNA codons. It has been shown that bacterial EFG is crucial to maintain the mRNA‐tRNA interaction during tRNA movement, as the absence or mutation of EFG leads to increased frameshifting and decreased translocation efficiency (Martemyanov et al , ; Savelsbergh et al , 2000a; Holtkamp et al , ; Peng et al , ; Zhou et al , ). An important parameter to maintain the mRNA reading frame is the interaction of mtEFG1 domain IV with the tRNA‐mRNA module via two apical loops that engage with the minor groove of the codon–anticodon base pairs and with the backbone of the peptidyl‐tRNA (Gao et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, the role of the downstream secondary structure element is to slow down the late stages of translocation (97,98,102,104). At this point the ribosome is stalled in a rotated or even hyper-rotated state in which the stabilizing contacts between the ribosome and the codon-anticodon complexes are dis- rupted, which allows the tRNA to sample alternative reading frames (78,102,111). Both the dissociation of the E-site tRNA and the backward rotation of the ribosomal subunits are slow, but the E-site tRNA is released before the ribosome rotates backwards (102).…”
Section: Spontaneous and Programmed Ribosome Frameshiftingmentioning
confidence: 99%
“…Both the dissociation of the E-site tRNA and the backward rotation of the ribosomal subunits are slow, but the E-site tRNA is released before the ribosome rotates backwards (102). EF-G, which usually restricts the A-site tRNA in the 0-frame position (78), can also dissociate prior to the completion of translocation (102). When both EF-G and the deacylated tRNA have been released, a single tRNA in transit from the A to the P site may be particularly prone to frameshifting (78).…”
Section: Spontaneous and Programmed Ribosome Frameshiftingmentioning
confidence: 99%
See 1 more Smart Citation
“…Chimeric hybrid orientations of tRNA have recently also been identified in T. thermophilus 70S ribosomes in the absence of elongation factor G 24 . One study found that a frameshift-suppressor tRNA binds in an intermediate orientation resembling a translocation intermediate 25 , and another study captured a translocation intermediate complex with two tRNAs in chimeric hybrid states 24 . It is likely that the structure we observe here resulted from the action of EF-G during the translation cycle in vivo.…”
Section: S Conformations In Five Cryo-em Classesmentioning
confidence: 99%